Collision and rebounding of circular rings on rigid target. (May 2015) - Xu, Shanqing; Ruan, Dong; Lu, Guoxing; Yu, T.X.
Abstract: The collision behaviour of three types of circular aluminium rings was experimentally studied in this paper. A specially designed fixture attached to the barrel of an air gun was employed for the lateral impact of flying rings on a rigid target. The force history, deformation mechanisms and rebounding velocity of the rings, as well as their dependence on the wall thickness of rings and initial impact velocity were extensively investigated. The results showed that larger initial velocity and greater non-dimensional thickness led to larger magnitude of peak force. With the increase of initial velocity, the rebounding velocity first increased to a maximum value and then dropped, while the coefficient of restitution first decreased almost linearly and then levelled off at a lower level. However, the wall thickness of the ring only has a limited influence on both the rebounding velocity and the coefficient of restitution within the studied range. A six-hinge deformation mechanism was identified based on the four-phase deformation mode of the ring during its collision, which was captured in high speed camera recordings. Furthermore, it was observed that the impact force history was highly related to the deformation mode. Highlights: Compressive tests were conducted on aluminium foams at intermediate strain rates from 1 to 200 s −1 . The strain rate effect on aluminium foams and honeycombs were reviewed and compared with data from various sources. The strength enhancement of aluminium foams and honeycombs were extensively studied and analysed. Possible reasons of the strength enhancement of aluminium foams and honeycombs under dynamic loadings were discussed.